Partial vertical ownership and tacit collusion - Frazão, Miguel Trigo Franco (2017)
A partial ownership held by a downstream rm creates a perceived cost asymmetry towards its competitors. In this article, it is shown that this will have a negative impact on the sustainability of a collusive scenario. This is a similar result to natural di¤erences in production costs of rms. However, this participation makes it so it is more likely to be the most e cient rm to deviate, and not the least one, as in natural assymetry. The existance of participation never makes collusion easier to sustain than its absence. This also creates a tool for the upstream rm to break, or incentivate, joint downstream decision-making, as it may also be used to increase its directed demand. Similarly, this tool can be used by a regulator to increase welfare by avoiding market concentration